(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Background: The use of social interaction web applications for health and wellbeing promotion has grown exponentially in current years. However, there are currently no social interaction web applications to assess knowledge and practice in the prevention of the spread of the novel coronavirus 2019 for the people in Thailand. The objective of this study was to develop a social interaction web application to assess knowledge and practice in the prevention of the spread of the novel coronavirus 2019. Methodology: The steps for creating a social interaction web application to assess knowledge and practice in the prevention of the spread of the novel coronavirus 2019 are described. The researchers developed the social interaction web applications based on the following procedures: 1) analyzing and identifying components of the social interaction web application; 2) creating a pilot design for the Web application; 3) developing the social interaction web application; 4) creating the supporting materials, and 5) evaluating and revising the social interaction web Application. Two hundred seventy peoples in Thailand used a social interaction web application and provided feedback to the developers. Result: Quantitative findings stated high to very high levels of satisfaction with the social interaction web application, regarding usefulness, convenience, quickness, and ease of access. Qualitative findings also provide evidence of the social interaction web application’s strengths and benefits, as well as challenges and obstacles. In conclusion: Thai people said that the web application useful and were satisfied with it. Widespread use of this innovative web application should be used to assess and sustain the knowledge and practice to prevent the spread of the novel coronavirus 2019, maintaining good health and promoting sustainable human well-being at all ages that is essential to the development of a healthy and sustainable society.